Coronaviruses disease 2019 (COVID-19): causative agent, mental health concerns, and potential management options (2020)
Coronavirus disease-2019 (COVID-19) pandemic started from Wuhan, China has infected more than 6.7 million individuals and killed more than 390,000 individuals globally. Due to the higher transmissibility and infectiousness, asymptomatic infection, and lack of effective treatment options and vaccine, fatalities and morbidities are increasing day by day globally. Despite physical health consequences, COVID-19 pandemic has created stress and anxiety, as result there is an increased risk of mental illnesses both in the infected and normal individuals. To eradicate these risks, it is necessary to determine the COVID-19 zoonotic source of transmission to humans and clinical manifestations in infected individuals. Although, identification or development of the highly effective therapeutic agents is necessary, however, development of protective strategies against the COVID-19 by enhancing immune responses will be an asset in the current scenarios of the COVID-19 pandemic. In this paper, we discuss the transmission, health consequences, and potential management (therapeutic and preventive) options for COVID-19 disease.